-1/9n+5=11

Simple and best practice solution for -1/9n+5=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/9n+5=11 equation:



-1/9n+5=11
We move all terms to the left:
-1/9n+5-(11)=0
Domain of the equation: 9n!=0
n!=0/9
n!=0
n∈R
We add all the numbers together, and all the variables
-1/9n-6=0
We multiply all the terms by the denominator
-6*9n-1=0
Wy multiply elements
-54n-1=0
We move all terms containing n to the left, all other terms to the right
-54n=1
n=1/-54
n=-1/54

See similar equations:

| -1/5x-22=-7 | | 5/7j-6=4 | | 2+3c=-2(-2c)+2(6) | | 4(w-8)=8 | | -1/10y-14=16 | | 3/7p+6=9 | | 9m+2=-20 | | 1,5X+5000=9x | | 3X+6000=9x | | −6(b+3)+9b=+3 | | 5^x^-3=25^x^-5 | | 5x-3=25x-5 | | -12x-7=53 | | 2z^2+15z-8=0 | | 10.2÷x=0.8 | | j=41-23 | | x^2−7x=8 | | 12x^2-48x+16=0 | | 3(x-2)-10(x-5)=-5 | | 7.3=u | | 3x^2-(58/8)x+2=0 | | 5x+14=10x | | m-18=62 | | m=11+16 | | -2/6p=3/6 | | p=35-12 | | 6-3=g | | 3=b-24 | | -3+6x=3(-1+5x)-9x | | z-9=67 | | 2x+7x=8x+1x | | c=7-3 |

Equations solver categories